Correction: Designing 3D-nanosubstrates mimicking biological cell growth: pitfalls of using 2D substrates in the evaluation of anticancer efficiency. Issue 44 (8th November 2021) - Patil, Ashwini; Nandi, Semonti; Kale, Narendra; Bobade, Chandrashekhar; Banerjee, Shashwat; Patil, Yuvraj; Khandare, Jayant
Abstract : Correction for 'Designing 3D-nanosubstrates mimicking biological cell growth: pitfalls of using 2D substrates in the evaluation of anticancer efficiency' by Ashwini Patil et al., Nanoscale, 2021, 13, 17473–17485, DOI: ; 10.1039/d1nr03816h .